Gestión comunitaria de residuos sólidos en gallito distrito de Fernando Lores-Loreto-Perú 2022 - Vela Pipa, Hanny Abigail (2025)
Solid waste management in the Gallito district, Fernando Lores, Loreto, faces significant challenges due to a lack of environmental awareness and insufficient infrastructure. The purpose of this study was to analyze waste management practices in the community, assess the residents' level of knowledge regarding waste classification, and propose solutions to improve solid waste management. The theoretical framework was based on community waste management, the importance of active public participation, and sustainable approaches such as recycling and composting. The methodology included surveys of district families, data analysis, and comparison with previous studies in rural communities. The results showed that 52.5% of families are unaware of solid waste or its classification, while practices such as burning and mixing waste remain common. However, 100% of the families support mandatory recycling. It is concluded that strengthening environmental education, improving waste infrastructure, and promoting community participation are essential to achieving sustainable waste management in Gallito.